MODELLING OF GLOBAL CAR MARKET DEVELOPMENT UNDER GLOBALIZATION IMPACT - O. Savych; E. Molchanova (Фінансово-кредитна діяльність: проблеми теорії та практики, 2019)
The aim of the article is to construct a model for the development of the market of passenger cars taking into account global impact, macroeconomics and marketing factors that enables automotive companies planning sales volumes, identifying potential markets for operational and efficient investments. The global processes as well as limitation in accessing to natural resources and their value increase, society digitalization, enforcement of competition and governmental regulations, all of them are key factors of car industry developments which have to be taken into account in the process of cars’ producers marketing activity. Another important impact factor is innovations as a basic pillar of enterprises’ competitiveness, which is functioning on the market. Therefore, the need in traditional approaches changes to marketing management under conditions of global changes in economy is very important for enterprises’ on car market, which are creating higher value for clients and moreover in long-term prospective such enterprises will have strong market positions. The results of research define main significant factors influencing sales on the global automotive market. Quantative model that has been developed, will allow to effectively plan the marketing activity of enterprises both on the global market and on their regional clusters. Furtemore, the research helps automotive manufactores with the entry market and efficient investments desisisions. The methodology of the quantative forecast measurament of cars’ sales both on global and its regional clusters is based on retrospective sales analysis and main quantitive impact factors. The quantative model has been checked by real sales data under retrospective figures that confirms its real practical ability.